PEMANFAATAN LEARNING MANAGEMENT SYSTEM (LMS) PADA MATAKULIAH SOFTWARE QUALITY ASSURACE - Dedy Syamsuar (Jurnal Sistem Informasi, 2010)
Traditionally, a learning process is conducted in face to face form. However, due to technology development, it can be carried out in a virtual class. With conventional class, lecturer and students have a limited time to interact or discuss about the course content or other things. To answer the limitations, the traditional method can be combined with the utilizing of ICT, in form of Learning Management System (LMS). The system which heavily relied on internet connection has been adopted widely by many universities all over the world. This paper reports the implementation of LMS at University Bina Darma, specifically in Software Quality Assurance course. This paper covers the features of the LMS and the implementation result of utilizing LMS in SQA learning process. Some general issues and challenges of such initiatives implementation will also be discussed. Nevertheless, although it creates a new challenge for the student, the result indicates that there are no major different between before and after using the media. Â  Keywords: LMS, elearning, metode pembelajaran